Potential of Gamelan Sekaten Reviewed from the Concept of 4A Tourism as a Traditional Cultural Tourism (Case Study on the Sekaten Ceremony to Commemorate the Maulid of Prophet Muhammad in Surakarta) - Abdul Aziz, Ahmad; Pitutur Thusto Gumawang; Nurmaria (International Journal of Travel, Hospitality and Events, 2025)
Purpose: This study was conducted with the aim of identifying the potential of Gamelan Sekaten performance in terms of the 4A components (attraction, amenities, accessibility and ancillary services) of tourism. Research Methods: This study uses a descriptive qualitative approach with a case study model. The informants in this study consist of 4 (four) participants, academics, event organizers, tourists and karawitan artists. The data collection method was carried out through interview and observation techniques. Data were analyzed using data reduction and thematic analysis techniques. Results and Discussion: The results of the study indicate that Gamelan Sekaten performance is considered to have more as a cultural tourism attraction for several reasons. Gamelan Sekaten performance has several differences when compared to other gamelan performances, such as its implementation which cannot be held at any time, but only at the Sekaten ceremony which is usually held to commemorate the Maulid Prophet Muhammad, and also, the use of gamelan musical instruments with a larger and more complex size and presenting gendhing or poems with a magnificent nuance are also characteristics of Gamelan Sekaten performance. Moreover, another aspect that makes gamelan sekaten more professional is the collaboration between event organizers and academics who has a background in karawitan arts education to keep the quality, uniqueness and authenticity of the performance. On the other hand, the result shows that there are few aspects related to 4A concept such as accessibility, amenities and ancillary services  that can be improved to increase tourist satisfaction to watch this performance. Implication: Gamelan sekaten performance is one of the cultural tourism attractions owned by the city of Surakarta that has proven to be able to attract tourists to visit and watch, both tourists from Indonesia, and even foreign tourist. The results have implications for improving several aspects based on 4A concept. Things that can be improved from accessibility aspect are accessibility in the venue and accessibility of performance information. Thing that can be improved from amenities aspect is quantity of facilities such as toilets and parking area. Thing that can be improved from ancillary services is the provision of tour guide to ensure the quality of visitor’s experiences and satisfaction. On the other hand. the research highlights the need to conduct similar research, especially using quantitative-based method, to measure the level of tourist satisfaction in visiting Gamelan Sekaten activity.